2005
DOI: 10.1007/s00701-005-0615-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of a basilar perforator aneurysm not accessible to endovascular treatment

Abstract: Aneurysms originating from perforatoring branches of the midbasilar artery are extremely rare. Rupture of such an aneurysm resulted in a subarachnoid hemorrhage with a prepontine clot in a 44 year old male who presented with an acute confusional state. After coil embolization had failed, the partially thrombosed aneurysm was wrapped and coagulated via a combined supra-/infratentorial subtemporal presigmoid approach in prone position. The postoperative course was complicated by a tension pneumatocephalus and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 6 publications
0
37
0
Order By: Relevance
“…Just as in 1 of the cases presented in this paper, basilar perforators can be inaccessible to catheterization 3,6,8 due to their small diameter, distal localization, and low blood flow. Surgery is often chosen as the first line of treatment, [4][5][6]8,12 including direct clipping, clipping of the parent vessel of the aneurysm, excision, trapping, wrapping, and coagulation. Endovascular techniques consist of coiling, stenting, or embolization.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…Just as in 1 of the cases presented in this paper, basilar perforators can be inaccessible to catheterization 3,6,8 due to their small diameter, distal localization, and low blood flow. Surgery is often chosen as the first line of treatment, [4][5][6]8,12 including direct clipping, clipping of the parent vessel of the aneurysm, excision, trapping, wrapping, and coagulation. Endovascular techniques consist of coiling, stenting, or embolization.…”
mentioning
confidence: 89%
“…Since first described by Ghogawala et al in 1996, 17 cases have been reported. [2][3][4][5][6][8][9][10]12 Since the beginning of 2012, at our institution we have encountered 3 ruptured perforator aneurysms of the posterior circulation. Those cases are reported in detail below.…”
Section: ©Aans 2014mentioning
confidence: 99%
See 1 more Smart Citation
“…55 In our review of the literature, we found 34 cases of posterior circulation aneurysms treated via the standard retrolabyrinthine posterior petrosal approach reported in 14 studies over the course of 2 decades (Table 3). 3,6,11,12,14,22,24,32,40,42,43,50,54,56 All aneurysms were completely occluded. In addition, although early morbidity was high (62%; 41% in the form of cranial nerve deficits), it was often transient.…”
Section: Posterior Petrosal Approachmentioning
confidence: 91%
“…They are also essential for the relay of sensory information between the cerebellum and cerebrum; as well as the regulation of respiration (1,2). The anatomic distribution of the pontine arteries (PAs), therefore, has been considered a crucial component of the arterial system in the lower brain, especially for surgical or endovascular treatment (3,4).…”
mentioning
confidence: 99%